Spatial modulation spectroscopy for imaging and quantitative analysis of single dye-doped organic nanoparticles inside cells1. Issue 21 (7th June 2015) - Devadas, Mary Sajini; Devkota, Tuphan; Guha, Samit; Shaw, Scott K.; Smith, Bradley D.; Hartland, Gregory V.
<x xml:space="preserve">Abstract</x> The loading and distribution of non-fluorescent dye-doped lipid-polymer nanoparticles in cells has been investigated by spatial modulation spectroscopy.